The Spread of Higher Education Around the Globe: A Cross-Country Analysis of Gross Tertiary Education Enrollment, 1999-2005. (March 2016) - Yu, Patricia; Delaney, Jennifer A.
Many nation-states have realized the importance of tertiary education and the world has seen a corollary increase in tertiary education enrollments. Using Berry and Berry's event history model as a framework, this study tests both the internal features of each country and the influence that nation-states have on each other with regard to setting tertiary enrollment policies. As expanding tertiary education is an important policy worldwide, we use Trow's classification to define two levels of tertiary education expansion: first, increasing gross tertiary enrollment rates above 15% (from elite to massified), and second, above 50% (from massified to universal). Analyzing a unique cross-national panel dataset, which spans the time period from 1999 to 2005, our findings show that both internal determinants (secondary education participation rates and the political landscape) as well as diffusion factors (proximity to a pioneering nation and regional variables) influence nations in setting tertiary enrollment policies.